HUBUNGAN ANTARA IDEAL DIRI DAN HARGA DIRI DENGAN OPTIMISME DALAM MENYELESAIKAN SKRIPSI PADA MAHASISWA TINGKAT AKHIR - Rafa Arinjani Pambayun; Bela Novita Amaris Susanto; Ayu Pratiwi (Indonesian Journal for Health Sciences, 2023)
Many students cannot complete their thesis within the allotted time, or even fail altogether. One of the factors is the lack of optimism that causes low self-esteem and negative self-ideals. The purpose of this study was to determine the relationship between ideal self and self-esteem with optimism in completing thesis in final year students. Quantitative research with a descriptive approach. A sample of 144 students was selected by purposive sampling technique. The research instrument used a questionnaire. Data analysis used the chi square test. The results showed that there were 27 students with positive self-ideals and good optimism. Negative self-ideal and lack of optimism, namely 117 students. Bivariate test results, p value 0.002 (0.05). Furthermore, students with high self-esteem and good optimism are 35 students. There are 109 students with low self-esteem and less optimism with bivariate test results, p value 0.004 (0.05). There is a relationship between ideal self and self-esteem with the optimism of final year students when completing their thesis.